Occupational exposure due to RF leakages within GSM base station cabins in eastern Nigeria (2012)
The occupational exposure due to RF radiation leaks inside the base station cabin, when working on the Base station Transceiver (BTS) Radios and TX cables and during active radio communication was measured. A total of number 30 base stations Cabins were studied in the eastern part of Nigeria, using a Broad band TES-90 Electrosmog meter. The maximum instantaneous electric field strength obtained from GSM 1800 radio was 3.72 V/m, 16.56 V/m for GSM 900 radio and 11.29 V/m for the Tx cables. The maximum instantaneous indoor and out power density were 35.47 mW/m2 and 6.64 mW/m2 respectively. Also, the average values of the obtained electric field strength from all the cabins are 1.18 ± 1.07 V/m from GSM 1800 radio, 2.33 ± 3.82 V/m from GSM 900 radio and 1.77 ± 2.20 V/m from the Tx cables. The result of this study shows that the values were less than ICNIRP limits for occupational exposure.